Cultural Imprints : An exhibition of artists in the Visual Arts Program, The Banff Centre. - Walter Phillips Gallery, The Banff Centre School of Fine Arts, Banff (Banff : Walter Phillips Gallery - The Banff Centre for the Arts Banff, 1987)
Andersen, Courtney ; Aziz, Sylvat ; Boulanger, Michel ; Elliott, Wendy ; Gaudette, George ; Ibata, Katsue ; Kui, Wang ; Lapointe, Jerome ; Moodie, Sharon ; Tang, Stanley ; Vilks, Janis ; Zero, Sam
Cultural Imprints : An exhibition of artists in the Visual Arts Program, The Banff Centre, Walter Phillips Gallery, Banff, December 10 - 23, 1987
boek